Two friends with eroded nodules on the ears: atypical fibroxanthoma case report - Filippo Pesapane; Gianluca Nazzaro; Luisa Lunardon; Antonella Coggi; Raffaele Gianotti (Sociedade Brasileira de Dermatologia, 2015)
AbstractAtypical fibroxanthoma is an uncommon mesenchymal tumor that manifests clinically as a reddish papule or nodule in sun-exposed areas of the body. The clinical presentation is not specific and histology and immunohistochemistry are both necessary for a correct diagnosis. Surgery is the gold standard of therapy. Recurrence and metastasis should be excluded with a follow-up at 6 months, since this tumor should nowadays be considered a medium-grade neoplasm, rather than low-grade as previously believed. We report the case of two friends who came to our hospital during the same period, complaining of very similar lesions. After biopsy and immunohistochemical examination, a diagnosis of atypical fibroxanthoma in both cases was formulated.